Reactive desorption electrospray ionization linear ion trap mass spectrometry of latest-generation counterfeit antimalarials via noncovalent complex formation. - Nyadong, L; Green, MD; De Jesus, V; Newton, P; Fernández, F (2007)
Desorption electrospray ionization mass spectrometry (DESI MS) is rapidly becoming accepted as a powerful surface characterization tool for a wide variety of samples in the open air. Besides its well-established high-throughput capabilities, a unique feature of DESI is that chemical reactions between the charged spray microdroplets and surface molecules can be exploited to enhance ionization. Here, we present a rapid screening assay for artesunate antimalarials based on reactive DESI. Artesunate is a vital therapy for Plasmodium falciparum malaria, but artesunate tablets have been counterfeited on a very large scale in SE Asia, and more recently in Africa. For this reason, faster and more sensitive screening tests are urgently needed. The proposed DESI assay is based on the formation of stable noncovalent complexes between linear alkylamines dissolved in the DESI spray solution and artesunate molecules exposed on the tablet surface. We found that, depending on amine type and concentration, a sensitivity gain of up to 170x can be obtained, in comparison to reagent-less DESI. Hexylamine (Hex), dodecylamine (DDA), and octadecylamine (ODA) produced proton-bound noncovalent complexes with gas-phase stabilities, increasing in the order [M + Hex + H]+ < [M + DDA + H]+ < [M + ODA + H]+. Tandem MS experiments revealed that complex formation occurred by hydrogen bonding between the amine nitrogen and the ether-like moieties within the artesunate lactone ring. After the reactive DESI assay was fully characterized, it was applied to a set of recently collected suspicious artesunate tablets purchased in shops and pharmacies in SE Asia. Not only did we find that these samples were counterfeits, but we also detected the presence of several wrong active ingredients. Of particular concern was the positive detection of artesunate traces in the surface of one of the samples, which we quantified with standard chromatographic techniques.